Associations of SARS-CoV-2 PCR positivity with clinical symptoms and race/ethnicity: The household transmission study - Sara H. Goodman; Jonathan Altamirano; Julianne Burns; Clea S. Sarnquist; Jennifer S. Read; Yvonne Maldonado (PLoS ONE, 2025)
Objective The objective of this study was to identify demographic and clinical factors associated with SARS-CoV-2 infection among household contacts (HCs) following exposure to a confirmed case. Methods We analyzed an existing case-ascertained prospective cohort study of 43 HCs of SARS-CoV-2-positive index cases recruited from Stanford Health Care between March 2020 and June 2022. Participants self-collected nasal swabs daily for up to 21 days for reverse transcription polymerase chain reaction (RT-PCR) testing and reported symptoms in daily diaries. Using Cox proportional hazards models, we assessed associations between participant characteristics over time to first positive PCR result. Results We found that symptomatology and race/ethnicity were independently associated with increased infection risk. In multivariable analysis, participants with systemic symptoms had a higher likelihood of testing positive (adjusted hazard ratio [aHR]=2.62; 95% confidence interval [CI]: 1.38–6.55). Additionally, identifying as a racial/ethnic minority had a greater risk of a positive test (aHR = 2.55 for systemic symptoms, 2.43 for any respiratory symptoms, and 2.40 for upper respiratory symptoms) compared to white patients. Conclusion These findings underscore the importance of symptom-based surveillance and highlight ongoing racial and ethnic disparities in SARS-CoV-2 transmission risk. This study also demonstrates the feasibility of longitudinal, self-administered testing and offers a scalable model for investigating transmission dynamics of respiratory viruses in community settings.